Exploring the role of the core in sports performance: a systematic review of the effects of core muscle training - Bustos Carvajal, Juan Sebastian; Arias Coronel, Florencio (Frontiers in Sports and Active Living, 2025)
IntroductionThe Core or central area of the body, is a group of muscles in charge of providing stability and postural control, being crucial in sports performance. In sports, the practice of exercises to strengthen this region can improve different performance variables. However, most of these programs in athletes focus on direct and specific strengthening of the extremities, largely ignoring the role that this part of the body can have on strength and power. Therefore, the aim of this study is to systematically review the literature on the effects of core muscle training on key athletic performance parameters in competitive athletes, focusing primarily on core strength, dynamic balance, sprint speed, jump height, and agility.Materials and methodsA systematic review was carried out using a search strategy applied to Scopus, Science Direct, WebScience, Sportdiscuss and Sage Journal databases. Randomized con-trolled trials, quasi-experimental studies and prospective observational cohort studies evaluating the effect of core training on performance in competitive athletes participating at regional, national, or international levels were included.ResultsCore training showed improvements in trunk extensor strength, core endurance, dynamic balance, and sprint speed in athletes. However, results regarding trunk flexor muscle strength, jump height and agility were not precise.ConclusionIn athletes, core training can improve core strength, dynamic balance, and sprint speed. However, its efficacy on other sports performan ce variables, such as agility or power, is not clear.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251036787, identifier CRD420251036787.